Virtual Educational Laboratories: Instructive or explorative learning? - Lisborg , Sanne (STS Encounters, 2021)
This paper explores how the field of Science and Technology Studies (STS) can inform and help conceptualise a relatively new form of laboratory work in education: virtual laboratories. To date, STS have not addressed laboratory work in education. This paper focuses on the virtual educational laboratory by synthesising arguments from the STS literature on laboratory work and proposes research questions that can guide future ethnographic research on how virtual laboratories are applied and constructed locally in the classroom. I argue that the virtual laboratory, like the physical one, must be understood in a broader cultural, social and material context. Moreover, the virtual laboratory has both constraints and affordances, tied to the medium through which it is materialised. I conclude that the virtual laboratory can be understood as a hybrid between explorative and instructive learning.